Comparison of the Quality of Life of Paraplegic Veterans and Disables; Case Study of Mazandaran Province, Iran - H. Tahmasebi; E. Abasi; M. Zafari; H. Darvish Gkezri (Afarand Scholarly Publishing Institute, 2016)
Aims: The quality of life of any person is affected by disabilities. However, the effects are not the same in persons with disabilities due to the accidence and in the veterans. The aim of this study was to investigate, as well as compare between, the quality of life in the paraplegic veterans and non-veterans in Mazandaran Province.   Instrument & Methods: In the analytic cross-sectional study, 29 paraplegic veterans, having been supported by the Martyrs and Veterans Foundation of Mazandaran Province, and 106 paraplegic persons, having been supported by the Welfare Organization of Mazandaran Province, were studied in 2015. The subjects were selected via stratified random sampling method. Data was collected by a demographic questionnaire, assessing age and the educational level, and the 36-Item Short Form Health Survey (SF-36), assessing the quality of life. Data was analyzed by SPSS 16 software using independent T and Chi-square tests.   Findings: The mean score of quality of life in the veterans (44.37±7.82) was significantly higher than the disables (36.57±7.94; p=0.0001). In addition, the mean scores of quality of life in the physical functioning, emotional role, mental health, social functioning, and general health in the veterans were significantly higher than the disables (p<0.05).   Conclusion: The quality of life of the paraplegic veterans and non-veterans of Mazandaran Province is unfavorable. In addition, the quality of life of the non-veteran disabled persons is lower than the veterans.